Tribbles pseudokinase 3 promotes enterovirus A71 infection via dual mechanisms - Huiqiang Wang; Ke Li; Boming Cui; Haiyan Yan; Shuo Wu; Kun Wang; Ge Yang; Jiandong Jiang; Yuhuan Li (Emerging Microbes and Infections)
Enterovirus A71 (EV-A71) is the main pathogen causing hand, foot and mouth disease (HFMD) in children and occasionally associated with neurological diseases such as aseptic meningitis, brainstem encephalitis (BE) and acute flaccid paralysis. We report here that cellular pseudokinase tribbles 3 (TRIB3) facilitates the infection of EV-A71 via dual mechanisms. In one hand, TRIB3 maintains the metabolic stability of scavenger receptor class B member 2 (SCARB2), the bona fide receptor of EV-A71, to enhance the infectious entry and spreading of the virus. On the other hand, TRIB3 facilitates the replication of EV-A71 RNA in a SCARB2-independent manner. The critical role of TRIB3 in EV-A71 infection and pathogenesis was further demonstrated in vivo in mice. In comparison to wild-type C57BL/6 mice, EV-A71 infection in TRIB3 knockdown mice (Trib3+/−) resulted in significantly lower viral loads in muscular tissues and reduced lethality and severity of clinical scores and tissue pathology. In addition, TRIB3 also promoted the replication of coxsackievirus B3 (CVB3) and coxsackievirus A16 (CVA16) in vitro. In conclusion, our results suggest that TRIB3 is one of key host cellular proteins required for the infection and pathogenesis of EV-A71 and some other human enteroviruses and may thus be a potential therapeutic target for combating the infection of those viruses.